ECOLOGICAL AND ECONOMIC MECHANISM OF SELECTION AND EVALUATION OF EFFICIENCY OF MEASURES TO REDUCE GREENHOUSE GAS EMISSIONS IN THE OIL AND GAS INDUSTRY - FADYEYEVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The problem of reducing greenhouse gas emissions is global in nature and requires not only the joint efforts of all countries, but also the use of effective mechanisms to address it. Greenhouse gas emissions from the oil and gas industry are a negative phenomenon associated with the extraction, storage, processing, transportation of hydrocarbons. They have a negative impact on the environment and the safety of human life.The development of modern approaches to the selection and comprehensive evaluation of the effectiveness of measures to reduce greenhouse gas emissions in the oil and gas industry is an urgent scientific problem that requires the development and implementation of advanced methods, especially today, when climate change has become one of the world's major environmental and economic problems. Global climate change is driven by a steady increase in greenhouse gas emissions, accompanied by an increase in the number of natural disasters and, as a result, the scale of economic losses. The type of target function for the assessment and selection of options for the implementation of environmental measures as a minimization of specific losses reduced to the unit of reduced greenhouse gas emissions is substantiated. It takes into account production, technological, environmental and social constraints and allows you to choose the option that provides the maximum reduction of greenhouse gas emissions in the oil and gas industry at minimum cost. An ecological and economic mechanism has been developed, which allows to reasonably choose measures to reduce greenhouse gas emissions taking into account all factors, to assess options for their implementation in the implementation of environmental activities in the oil and gas industry.
Keywords: efficiency; economic losses; ecological and economic mechanism; greenhouse gas emissions; emission reduction measures